Temperatura como modulador da germinação de três espécies de Bromeliaceae - Alexandre Aparecido Duarte (2015)
This study aimed at evaluating the effect of temperature in the germination of seeds of three rupestrian field bromeliads of Serra da Piedade, Vriesea friburgensis (Mez), Vriesea bituminosa Wawra, Racinaea aerisincola (Mez), M. A. Spencer & L. B. Sm. In chapter 1, it was aimed at testing the hypothesis that the germination response of those species shows the same pattern found more than one decade ago. For this study, seeds were collected and submitted to constant temperatures of 10, 15, 20, 25, 30, 35 and 40 °C under light and dark conditions. The results showed some difference in the germination response related to the tested variants (light and temperature). Those variants affected in a significant way the percentage of germination and the average time of germination of R. aerisincola and V. bituminosa seeds, The germination percentage of V. friburgensis seeds was affected significantly only by different temperatures. The results confirmed the hypothesis that those species maintained the germination pattern found more than a decade ago. In chapter 2 the thermal model to describe the germination of V. friburgensis, V. bituminosa and R. aerisincola species in constant temperatures under light or dark condition was analyzed. Germination results and speed of germination of different percentage fractions of seeds of the three species were obtained from data of the first part of this study and were used in the analysis of the thermal-time model. It was determined by the regression of the fractional speed of germination in relation to the temperature and the probit regression of cumulative germination in relation to the amount of degrees per day, as well as minimum (Tb), very good (To) and maximum (Tc) temperature parameters of germination and the amount of degrees per day (T) needed to individual germination of the seeds. The species showed different Tb, To and Tc in relation to the presence or absence of light. Tb values obtained by the two methods were similar to the analyzed species. The thermal-time model described with accuracy the germination response of seeds of V. friburgensis and V. bituminosa species, the same was not observed to R. aerisincola specie.